Effectiveness of extension training methods in educating the fisherwomen in two fishing centers - S., Balasubramaniam (Fishery Technology, 2025)
The paper presents the socio-personal characteristics of trainees and the effectivenessÂ of training methods in two fishing centers viz. Kollam and Kasaba. Out of two treatmentsnamely demonstration with discussion, and demonstration with lecture and discussion, eachÂ one was used in a centre for training the respondents. The results revealed that in termsof knowledge, there were significant gains in knowledge scores of trainees (35.36% and 28.61%)Â in the two training centers where the two training treatments were used. In terms of attitude,Â by using lecture + demonstration + group discussion methods, there was found to be aÂ significant gain (10.97%) after the training. By using demonstration + discussion methods,Â there was found to be a slight reduction (-2.68%) in the attitude scores after the trainingÂ when compared with the ’Before training’ scores. In terms of skill learnt, it was found thatÂ in both treatments, the trainees had gain in skill scores (60.97% and 36.11%). Thus theÂ results implied that lecture + demonstration + discussion methods were found to be moreeffective in changing the knowledge, attitude and skill scores of trainees.